THE INFLUENCE OF BRANDING CREDIBILITY ON WORD OF MOUTH THROUGH CUSTOMER SATISFACTION AND CUSTOMER SATISFACTION AND CUSTOMER LOYALTY AT INDOMARET SURABAYA SUPERMARKET - Angelina Gayatri; Elyzabet Gultom; Imelda Fransisca; Trifena Ferren Tiwow (Indonesian Marketing Journal, 2022)
This article provides analysis for retail developments to retain customers and acquire new customers, rapid business development, and tight business development can affect certain variables. The method used is the brand credibility method by creating satisfaction and loyalty to a word of mouth that can have a positive impact on customers and businesspeople. The research approach used is the technical research of Indomaret Swalayan respondents by means of an approach between customers as consumer actors.